Heat nonlinearity of surface waves at interface between finite gas pressure magnetized plasma and metal - Akimov, Yu.A.; Azarenkov, N.A.; Olefir, V.P. (Вопросы атомной науки и техники, 2003)
This report is devoted to the investigation of the non-linear mechanism of plasma electrons heating on dispersion properties of potential surface waves (SWs) that propagate along interface of metal-magnetized plasma of a finite pressure. The external steady magnetic field is perpendicular to the medium interface. The different mechanisms of electron energy losses in approach of a weak heating are considered. The spatial distribution of plasma electron temperature on the basis of energy balance equation in framework of the non-local electrons heating is obtained. The nonlinear shift of wavenumber and spatial attenuation coefficient at different plasma parameters are researched. The obtained results are valid both for semiconductor and gas plasma.